(untitled) - Jameson, Gregory W (New York, 1989)
This book illustrates site construction details in a consistent and uniform drawing format of line types and lettering styles. This concepts is to provide the user with a unified system of hundreds of construction details. These construction details cover a wide range of topics for site planning, engineering and landscape architectural design
Keywords: architecture,building sites,computer; details,data processing,planning,data processing,aided design